Asymmetric government expenditure: a comparison of advanced and developing countries. Issue 2 (3rd April 2019) - Çulha, Ali Aşkın
Abstract : This paper studies the responsiveness of government expenditures to business cycles and introduces an index of asymmetric government expenditures using panel data for advanced and developing countries during the period 1981–2014. The empirical findings show that government expenditures tend to be procyclical in developing countries but acyclical in advanced economies. In addition, it is found that government expenditures respond in a countercyclical manner during bad times in advanced countries, but in a strongly procyclical manner during good times in developing countries. The index of asymmetric government expenditures for developing countries tends to be higher than that of the advanced countries.